Total Replacement of Sodium Selenite by Selenium Yeast Reduces non Prime Cuts Yields in Male Broilers - Goncalves , Fernanda M.; Nunes, Juliana K.; Novelini, Liliane; Manzke, Naiana E.; Anciuti, Marcos A.; Rutz, Fernando; Zanusso, Jerri T. (International Journal of Poultry Science, 2012)
The objective of this study was to evaluate carcass traits, yield and meat quality of broilers supplemented with organic selenium (selenium yeast) in total replacement to sodium selenite in the diets. A total of 704 male Cobb chicks, one day old, were randomly allotted in 32 boxes, which one with 22 animals, in a total of 16 replicates per treatment. The diets were formulated based on corn and soybean meal and different sources of selenium. The treatments consisted of selenium in the inorganic form (sodium selenite, SS) and in an organic form (selenium yeast, SY) supplementation. At 42 days old, 64 birds per treatment were slaughtered and carcass traits, yields and meat quality were evaluated. SY group showed lower back yield in comparison with SS group. Breast yield was slighted higher in SY group, however, no statistic differences were found. Meat quality and traits were not influenced by dietary treatments. Total replacement of sodium selenite by selenium yeast in broilers diets reduces back yields, a non prime cut in chicken carcass. Sodium selenite can be totally replaced by selenium yeast without affecting broiler meat quality and traits.